2012
DOI: 10.5923/j.food.20120203.02
|View full text |Cite
|
Sign up to set email alerts
|

Production and Effect of Storage in the Chemical Composition of Mozzarella Cheese

Abstract: The present study aimed at the determining the storage stability of the yield and the physico-chemical characteristics of mozzarella cheese prepared from cow milk, goat milk and a mixture of cow and goat milk. The cheeses were subjected to the analyses during different storage periods (first day , 15 th day and 30 th day after manufacturing). Mozarella cheese contained appreciable amounts of minerlas, calcium, sodium, phosphorus and potassium throughout the storage period. The pH ranged (4. 93 -5.21, 4.83 -5.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…The findings of the present study agree with the findings of many researchers (Pizaia et al, 2003;Indumathi et al, 2013;Seth and Bajwa, 2015;Waheed et al, 2017). However, Sulieman et al (2012) have reported much lower titratable acidity in cow's milk mozzarella cheese (0.203±0.01%) and goat milk mozzarella cheese (0.13±0.01%), respectively. On the contrary, El-Tahra et al ( 2008) reported higher acidity of cow's milk mozzarella cheese and it was attributed to the incorporation of 0.5 and 1.0% of whey protein to the cow's milk.…”
Section: Titratable Aciditysupporting
confidence: 92%
See 1 more Smart Citation
“…The findings of the present study agree with the findings of many researchers (Pizaia et al, 2003;Indumathi et al, 2013;Seth and Bajwa, 2015;Waheed et al, 2017). However, Sulieman et al (2012) have reported much lower titratable acidity in cow's milk mozzarella cheese (0.203±0.01%) and goat milk mozzarella cheese (0.13±0.01%), respectively. On the contrary, El-Tahra et al ( 2008) reported higher acidity of cow's milk mozzarella cheese and it was attributed to the incorporation of 0.5 and 1.0% of whey protein to the cow's milk.…”
Section: Titratable Aciditysupporting
confidence: 92%
“…Based on the different types of milk used for the preparation of ironfortified mozzarella cheese, the pH of goat milk cheese samples (5.45±0.01) was significantly lower (p<0.01) than cow (5.70±0.05) and mixed milk cheese samples (5.74±0.10) in the control group while in the treatment group cow's milk cheese samples (5.10+0.07) were significantly lower (p<0.01) that goat milk (5.56+0.01) and mixed milk cheese samples (5.54+0.02), respectively (Table 1). Similar pH values were reported by Sameen et al (2002) and Sulieman et al (2012) for cow's milk cheese. However, the pH values of control groups were slightly higher in the present study which may be attributed to a higher cooking temperature that tends to increase syneresis, reduce curd moisture and lactose and lactate contents, resulting in lower lactate to protein ratio and higher buffering capacity in cheese, thereby increasing the pH values of the end product.…”
Section: Phsupporting
confidence: 87%
“…In addition, cheese is a dairy product and is generally rich in milk casein, lipids and minerals, materialized here by high ash content [61]. It is also richer in Ca, P and Na than legumes [61]. On the other hand, legumes are richer in carbohydrates, K, Fe, Zn and Cu, which explains the results obtained in the optimum bread [31].…”
Section: Pasting Properties Of Sour Cassava Starch Cowpea Flour Peanu...mentioning
confidence: 92%
“…The cheese bread is higher than our optimal bread; this can be explained by the fact that the rate of incorporation of cheese (54%) in the formulation is higher than that of legumes (26%). In addition, cheese is a dairy product and is generally rich in milk casein, lipids and minerals, materialized here by high ash content [61]. It is also richer in Ca, P and Na than legumes [61].…”
Section: Pasting Properties Of Sour Cassava Starch Cowpea Flour Peanu...mentioning
confidence: 99%
“…Hot brine (70°C) was added to curd and mixed well until a homogenized paste was obtained. At 6°C, the curd was added in iced brine (12%) for 6 h. After 4 h, the curd was dried, and cheese was packed in sterile plastic bags and stored at 4°C for further analysis (Sulieman et al 2012).…”
Section: Cheese Productionmentioning
confidence: 99%